Salmonella and Caspase-1: A complex Interplay of Detection and Evasion - Miao, Edward A.; Rajan, Jayant V. (Frontiers in Microbiology, 2011)
Salmonellae are intracellular pathogens that replicate within epithelial cells and macrophages, and are a significant public health threat in both developed and developing countries. The innate immune system detects microbes through pattern recognition receptors, which are compartmentalized on the subcellular level to detect either extracellular (e.g. TLRs) or cytosolic (e.g. NLRs) perturbations. Salmonella infection is detected by the NLRC4 and NLRP3 inflammasomes, which activate Caspase-1, resulting in reduced bacterial burdens during infection. NLRC4 responds to the SPI1 type III secretion system via detection of inadvertently translocated flagellin and rod protein. The signals for NLRP3 detection during Salmonella infection remain undefined. Salmonella have evolved evasion strategies to attenuate Caspase-1 responses. We review recent findings describing the interplay between detection and evasion of S. typhimurium infection by the inflammasome. We discuss how the interplay between detection and evasion affects Caspase-1 effector functions mediated by IL-1β secretion, IL-18 secretion, and pyroptosis.